Dynamics of Ethical Considerations in Independent Auditor Decisions - Febriyanti, Diah; Sudaryo, Yoyo (Riviera Publishing, 2025)
This study examines the influence of professionalism, independence, and social responsibility on ethical judgment. This research is motivated by the frequent occurrence of audit failures, which are often linked to indications of ethical code violations by public accountants. Audit failure is not only experienced by small and medium-sized public accounting firms but also by firms categorized within the Big Four, which have faced similar cases involving suspected ethical breaches by public accountants. The research method employed in this study is a quantitative approach. The population consists of public accountants in Bandung. The sampling technique used is purposive sampling. Based on this technique, 56 public accountants met the criteria during the observation period. Hypothesis testing was conducted using multiple regression analysis. The results indicate that professionalism, independence, and social responsibility significantly influence ethical judgment. The higher the levels of professionalism, independence, and social responsibility, the better the moral judgment of public accountants.